PENDIDIKAN AGAMA ISLAM BAGI ANAK PADA KELUARGA PEKERJA DI DESA WAEYASEL KABUPATEN MALUKU TENGAH - Astriani Waly (IAIN Ambon, 2022)
Abstract: This study aims to determine Islamic religious education for children in working families in Waeyasel village, Central Maluku district. The questions to be answered through this research are: 1) how is Islamic religious education for the children of fishermen, farmers and teachers in Waeyasel Village. 2) how to implement Islamic religious education for children in Waeyasel village. 3) what are the inhibiting and supporting factors of Islamic religious education for children in working families in Waeyasel Village. The method used in this research is qualitative method. Data collection techniques in the form of observation, interviews and documentation. as well as data analysis techniques in the form of stages, data reduction, and data presentation and draw conclusions the research was carried out for one month. Based on the results of the study that there are three educations applied by working parents: first, worship education, parents teach how to worship, both mandatory worship and sunnah worship. such as prayer, fasting, reading and the Qur'an, secondly, parental moral education teaches their children how to eat well, make friends, be polite to parents and respect elders, thirdly, aqidah education instills confidence and faith that God exists. and always see and supervise him in every action he does, what parents teach to their children makes the child accustomed to doing the things his parents taught him. Keywords: Islamic religious education, children, families, workers Abstrak: Penelitian ini bertujuan untuk mengetahui pendidikan agama Islam bagi anak pada keluarga pekerja di desa waeyasel kabupaten Maluku tengah. Pertanyaan yang ingin dijawab melalui penelitian ini adalah: 1) bagaimana pendidikan agama Islam bagi anak nelayan, petani dan guru di Desa waeyasel. 2) bagaimana implementasi pendidikan agama Islam bagi anak di desa waeyasel. 3) apa saja faktor-faktor penghambat dan pendukung pendidikan agama islam bagi anak pada keluarga pekerja di Desa waeyasel. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Teknik pengumpulan data berupa observasi, wawancara dan dokumentasi. serta teknik analisis data berupa tahap , reduksi data, dan penyajian data dan menarik kesimpulan penelitian dilaksanakan selama satu bulan. Berdasarkan hasil penelitian bahwa ada tiga pendidikan yang diterapkan orang tua pekerja: pertama pendidikan ibadah, orangtua mengajarkan bagaimana cara ibadah, baik ibadah wajib maupun ibadah sunnah. seperti shalat, puasa, membaca dan Al Qur’an, kedua, pendidikan akhlak orangtua mengajarkan kepada anaknya bagaimana adab makan yang baik, adab berteman, sopan santun pada orangtua dan menghormati yang lebih tua,ketiga pendidikan aqidah menanamkan keyakinan dan keimanan bahwa Allah itu ada dan selalu melihat serta mengawasinya dalam setiap perbuatan yang ia lakukan, apa yang diajarkan orangtua kepada anaknya membuat anak tersebut terbiasa melakukan hal-hal yang diajarkan orangtuanya. Kata kunci: pendidikan agama islam, anak, keluarga, pekerja.